2016
DOI: 10.1111/ene.13052
|View full text |Cite
|
Sign up to set email alerts
|

Is there a significant interaction effect between apolipoprotein E rs405509 T/T and ε4 genotypes on cognitive impairment and gray matter volume?

Abstract: Background Evidence demonstrates that the T allele of the single-nucleotide polymorphism rs405509 in the apolipoprotein E (APOE) promoter is a risk factor for Alzheimer’s disease (AD). However, it is unknown whether rs405509 T allele synergizes to the APOE ε4 allele in influencing cognition and brain structure. Methods We analyzed the interaction of the rs405509 T allele and the APOE ε4 allele on cognitive ability and brain gray matter volume (GMV) among the elderly people. The subjects were grouped into fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 55 publications
2
23
0
Order By: Relevance
“…To that end, we are currently exploring the hypothesis that there is an association between either variant rs405509 (-219G/T) or rs769446 (-427T/C) and WMH development. These variants have been associated in the past with brain functional decline and may be a confounding factor in altitude-induced injury [ 14 , 15 ]. We anticipate developing a better understanding of ApoE ’s role in altitude-related negative effects through the currently reported results regarding ApoE status and the up-coming work on promoter genotypes.…”
Section: Main Textmentioning
confidence: 99%
“…To that end, we are currently exploring the hypothesis that there is an association between either variant rs405509 (-219G/T) or rs769446 (-427T/C) and WMH development. These variants have been associated in the past with brain functional decline and may be a confounding factor in altitude-induced injury [ 14 , 15 ]. We anticipate developing a better understanding of ApoE ’s role in altitude-related negative effects through the currently reported results regarding ApoE status and the up-coming work on promoter genotypes.…”
Section: Main Textmentioning
confidence: 99%
“…Promoter polymorphisms may increase the dementia risk through the APOE4 pathway (Rantalainen et al, 2019 ), with expression levels of APOE4 determined by APOE promoter polymorphisms (Lescai et al, 2011 ). Previous studies have found that rs405509 T homozygosity can modulate the effect of APOE4 on both cognitive performance and brain structure (Ma et al, 2016a , b ). TT carriers with APOE4 suffered from a poor cognitive status and reduced GMV in the inferior temporal gyrus and fusiform gyrus, and more importantly, the cognitive and structural changes were significantly correlated (Ma et al, 2016b ).…”
Section: Discussionmentioning
confidence: 96%
“…Previous studies have found that rs405509 T homozygosity can modulate the effect of APOE4 on both cognitive performance and brain structure (Ma et al, 2016a,b). TT carriers with APOE4 suffered from a poor cognitive status and reduced GMV in the inferior temporal gyrus and fusiform gyrus, and more importantly, the cognitive and structural changes were significantly correlated (Ma et al, 2016b). This correlation may reflect the neuromechanism of gene interaction at the brain level and contribute to low cognitive function (Ma et al, 2016b).…”
Section: The Potential Pathological Mechanism Of Rs4055059 On Cognitimentioning
confidence: 99%
“…Indeed, cognitive deficits are often thought to be associated with brain functional and/or structural impairments [ 28 , 29 ], which can be measured by using volumetric or functional magnetic resonance imaging (MRI) neuroimaging techniques. For example, resting state blood-oxygen-level dependent (BOLD) MRI allowed the delineation of the human neural functional architecture into multinetworks, such as the default mode network (DMN) and frontal-parietal network (FPN) [ 30 ].…”
Section: Introductionmentioning
confidence: 99%